ANALISIS PROFITABILITAS TERHADAP EFISIENSI OPERASIONAL DI PERBANKAN SYARIAH - Muhlis Muhlis; Agus Toni; Fadia Ayu Ningrum (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2021)
The Bank is financial institution has an important role in economy of country. Tge right profitability performance banks is indispensable for the functioning continuity of bank as intermediary institutions. The research analyze effect of return on asset (ROA) and return on equity (ROE) as a profitability on the operational efficiency between 2019-2020. Data were analyzed using method multiple linier regression. The results of this research indicate that partially ROA have a negative and significant effect operational efficiency, ROE has a positive but not significant effect on operational efficiency.